Compensatory Cross-Modal Plasticity Persists After Sight Restoration - Mowad, Theresa G.; Willett, Aimee E.; Mahmoudian, Mani; Lipin, Mikhail; Heinecke, Armin; Maguire, Albert M.; Bennett, Jean; Ashtari, Manzar (Frontiers in Neuroscience, 2020)
Sensory deprivation prompts extensive structural and functional reorganizations of the cortex resulting in the occupation of space for the lost sense by the intact sensory systems. This process, known as cross-modal plasticity, has been widely studied in individuals with vision or hearing loss. However, little is known on the neuroplastic changes in restoring the deprived sense. Some reports consider the cross-modal functionality maladaptive to the return of the original sense, and others view this as a critical process in maintaining the neurons of the deprived sense active and operational. These controversial views have been challenged in both auditory and vision restoration reports for decades. Recently with the approval of Luxturna as the first retinal gene therapy (GT) drug to reverse blindness, there is a renewed interest for the crucial role of cross-modal plasticity on sight restoration. Employing a battery of task and resting state functional magnetic resonance imaging (rsfMRI), in comparison to a group of sighted controls, we tracked the functional changes in response to auditory and visual stimuli and at rest, in a group of patients with biallelic mutations in the RPE65 gene (“RPE65 patients”) before and 3 years after GT. While the sighted controls did not present any evidence for auditory cross-modal plasticity, robust responses to the auditory stimuli were found in occipital cortex of the RPE65 patients overlapping visual responses and significantly elevated 3 years after GT. The rsfMRI results showed significant connectivity between the auditory and visual areas for both groups albeit attenuated in patients at baseline but enhanced 3 years after GT. Taken together, these findings demonstrate that (1) RPE65 patients present with an auditory cross-modal component; (2) visual and non-visual responses of the visual cortex are considerably enhanced after vision restoration; and (3) auditory cross-modal functions did not adversely affect the success of vision restitution. We hypothesize that following GT, to meet the demand for the newly established retinal signals, remaining or dormant visual neurons are revived or unmasked for greater participation. These neurons or a subset of these neurons respond to both the visual and non-visual demands and further strengthen connectivity between the auditory and visual cortices.